Analysis of Fe and Zn content in green mussell Perna viridis at Bandengan beach Jepara and Tanjung Mas beach Semarang city - Anita Dwi Kartika; Delianis Pringgenies; Ali Ridlo (Masyarakat Moluska Indonesia, 2019)
Green Mussel included to permanent animal so the interaction with its environment will affect its needed or its un-needed nutrient. Iron and zinc represent a very required micro mineral of human body. Iron plays an important role in forming red corpuscles and preventing anemia. The function and role of zinc in body for example to assist the forming of cell genetic items, forming the red corpuscle (haemoglobin), and also to assist pancreas function in digestion process. Territorial water of Jepara and Semarang are the representation areas producing Green Mussel (Perna Viridis). The aim of this research is to understand the iron and zinc content in Green Mussel. This research was conducted in December 2006 until February 2007. Materials used in this research is Green Mussel derived from Territorial water of Bandengan, Jepara and Territorial Water of Tanjung Mas, Semarang. The intake of Green Mussel sample used Purpose Random Sampling Method, which is intake of sample at random according to specific purpose. Method used in this research is Descriptive Method, while for iron and zinc measurement method using AAS. The result showed that the iron rate in Green Mussel at Territorial Water of Bandengan, Jepara degraded 459,70, 209,23 and 147,87 mg/kg from December 2006 until February 2007. While the Iron content in Green Mussel at Territorial Water of Tanjung Mas, Semarang continuously increased 227,18, 317,66 and 336,52 mg/kg from December 2006 until February 2007. The analysis result of zinc content on December until February of Jepara degraded 60,15, 8,90 and 7,73 mg/kg. While the Green Mussel Zinc of Tanjung Mas, Semarang on December 2006 until January 20.07 was degrading, from 154,10 become 9,63 and on January until February was increasing, from 9,63 mg/kg become 10,11 mg/kg.